Luminescence effects in reactive powder sintered silica glasses for radiation sensing. Issue 1 (26th July 2018) - Shaw, Ruth E.; Kalnins, Christopher A. G.; Spooner, Nigel Antony; Whittaker, Carly; Grimm, Stephan; Schuster, Kay; Ottaway, David; Moffatt, Jillian Elizabeth; Tsiminis, Georgios; Ebendorff‐Heidepriem, Heike
Abstract: Silica glasses doped with rare‐earth ions are potential materials for optical fiber radiation detection and dosimetry applications. High sensitivity to radiation requires fibers with large cores that can be reliably fabricated using glass made in a novel process from the reactive powder sintering of silica. The luminescence and dosimetric properties of a range of rare earth‐doped silica materials produced using this novel technique are reported here. Radioluminescence and optically stimulated luminescence (OSL) are the fundamental mechanisms enabling radiation detection in optical fibers. It was found that thermoluminescence, radioluminescence, and OSL are observed if the glass contains luminescent transitions in the detection wavelength range. Cerium‐ and thulium‐doped silica glasses were found to be promising candidates for optical fiber dosimetry. Samples showed intense luminescence signals in response to both photo‐stimulation and irradiation from alpha and beta sources. OSL results for cerium are three times larger than results for irradiated fluoride phosphate glasses previously tested for dosimetry use. Spectroscopic measurements indicate emission in the 300‐500 nm region, suitable for detection with photomultiplier tubes.